GAMBARAN TIPE KEPRIBADIAN PENDERITA HIPERTENSI DI POLI DALAM RSUD GAMBIRAN KOTA KEDIRI - RISNASARI, NORMA (Universitas Nusantara PGRI Kediri, 2015)
AbstractHypertensionisadisorderin the circulatory system, that caused of the human health. Generally, it washappened to the middle-age (in age over40years). There arevarious factorsthatlead ofhypertension. Forexample, age, gender, family history of hypertension, DiabetesMellitus,Obesity, consumption offoodswithhighsalt content, habits(stressful lifestyle).The purposeofthis researchwas to determine thepersonalitytype of descriptionPolyinPatients withhypertensioninhospitalsGambiranKediri.The research designused wasdescriptive, withthe entirepopulationof hypertensive patientsat Poli DalamRSUDGambiran Kediri. The technique is purposive sampling. Samples obtainedwere26respondents, and collectiondata usedquestionnaires.Results of the study, of26respondentsalmosthalfof respondentsie 10(39%) of respondentshave apersonalitytypesanguinanda minority of respondents, a littleresponden has 3(12%) ofrespondentshaveassertivepersonality type.Thus, the writer expected to the patient of hipertention can change the type of sanguin individuality becomeassertive individuality. In give statement and the opinion, idea and arguement with explicit, critical but havesmooth feeling till it do not make others people broken heart. To strunggle for endure their patent right, but itnot threaten others right too, it can be able to express their feeling by themselves with manner. Tiil it can notcause upgrading of blood pressure.Keywords: Personality, Hypertension